Tinjauan Layanan Pembiayaan Berbasis Teknologi Informasi Berdasarkan Prinsip Syariah Dalam Fatwa DSN-MUI Nomor 117/DSN-MUI/II/2018: (Studi Kasus Danasyariah.id) - Tri Wulandari , Septi; Nasik, Khoirun (MADINAH, 2019)
Facing the Covid-19 pandemic era clearly presents new challenges for the parties involved, both personal and corporate businesses, even in the territory of the country. Along with the development of the halal lifestyle, some Muslims in Indonesia have had a lot of influence on the Islamic financial industry, including fintech. An innovation in peer to peer financing services, which is an online-based lending and borrowing system that brings together fund recipients and funders by utilizing information technology through the platform company's. The focus of the problem outlined in this discussion is whether the implementation of information technology-based financing services based on sharia principles at PT. Dana Syariah Indonesia are in accordance or not with the Fatwa of the National Sharia Council-Indonesian Ulema Council No. 117/DSN-MUI/II/2018. This research uses an empirical juridical approach, namely legal research on primary data or legal regulations which is then linked to the practice of the financing system in the field. The analysis was carried out qualitatively by implementing religious legal norms issued by the DSN-MUI in Fatwa No. 117/DSN-MUI/II/2018 concerning Information Technology-Based Financing Services Based on Sharia Principles. The results of this study indicate that the object of the company fintech PT. Dana Syariah Indonesia, the concept peer to peer financing can connect financiers with financing recipients on one platform. One of these financing recipients can be funded by a pool of funds that have been successfully collected from several financiers. Where in the end, the financiers will get a share of the margin (profit funds) that has been lent with terms and conditions that are binding on both parties. In the analysis of the DSN-MUI Fatwa No. 117/DSN-MUI/II/2018 concerning Information Technology-Based Financing Services based on Sharia Principles are substantially appropriate, it's just that in practice the contract wakalah is given by the recipient of the financing and the contract is murabahah carried out simultaneously, while in the fatwa in principle, it is explained that the akad murabahah can occur after the goods are owned by the organizer, namely PT. Dana Syariah Indonesia, because fatwas are more prudent. However, there is no prohibition in sharia.